A evolução da mesóclise - Haffner, Ildikó (Acta Hispanica, 2009)
The aim of the paper is to give an overview of the development of mesoclisis, a peculiar area of pronominal clitic placement. Mesoclisis is a particular instance of enclisis (Verb-clitic) when a clitic is placed inside a morphological word, surfacing in between the verbal root and the inflectional suffixes. Mesoclisis only appears with future and conditional forms of the verb, clearly showing the origins of the inflexion, namely the Vulgar Latin auxiliary, habere. In most Romance language the analytic future and conditional became synthetic at an early stage and could not be divided by a constituent (clitic) but in Old Spanish and Portuguese mesoclisis was still a preferred option. It was also natural for both Spanish and Portuguese authors to use the mesoclitic form in the 16th century. With the explosive growth of proclisis (clitic-Verb) in Spanish, mesoclisis became gradually unused and disappeared, whereas Portuguese preserved this archaic structure and it is still in use if there is no triggering condition in the sentence (negation, wh question, adverbs, etc.) Today they are in complementary distribution with enclisis and well defined rules set their use, it is the morphology of the verb that defines the choice.